2007
DOI: 10.1007/s00425-007-0562-7
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effect of dark-chilling on chloroplast structure and arrangement of chlorophyll–protein complexes in pea and tomato: plants with a different susceptibility to non-freezing temperature

Abstract: The eVect of dark-chilling and subsequent photoactivation on chloroplast structure and arrangements of chlorophyll-protein complexes in thylakoid membranes was studied in chilling-tolerant (CT) pea and in chillingsensitive (CS) tomato. Dark-chilling did not inXuence chlorophyll content and Chl a/b ratio in thylakoids of both species. A decline of Chl a Xuorescence intensity and an increase of the ratio of Xuorescence intensities of PSI and PSII at 120 K was observed after dark-chilling in thylakoids isolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 66 publications
6
38
0
2
Order By: Relevance
“…Visualization of chlorophyll a fluorescence by confocal laser scanning microscopy (CLSM) enabled observation of the natural lipid membranes containing the chlorophyll-protein complexes (e.g., inside intact chloroplasts or leaves) without any fixation procedure and in situ (Mehta et al, 1999;Garstka et al, 2005Garstka et al, , 2007Hasegawa et al, 2010;Rumak et al, 2010Rumak et al, , 2012. Red fluorescence was attributed mainly to chlorophyll a species emitted at around 680 nm, because at room temperature the long-wavelength emission, above 700 nm, was rather weak (Mehta et al, 1999;Hasegawa et al, 2010).…”
Section: Confocal Laser Scanning Microscopy Of Lipid-protein Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Visualization of chlorophyll a fluorescence by confocal laser scanning microscopy (CLSM) enabled observation of the natural lipid membranes containing the chlorophyll-protein complexes (e.g., inside intact chloroplasts or leaves) without any fixation procedure and in situ (Mehta et al, 1999;Garstka et al, 2005Garstka et al, , 2007Hasegawa et al, 2010;Rumak et al, 2010Rumak et al, , 2012. Red fluorescence was attributed mainly to chlorophyll a species emitted at around 680 nm, because at room temperature the long-wavelength emission, above 700 nm, was rather weak (Mehta et al, 1999;Hasegawa et al, 2010).…”
Section: Confocal Laser Scanning Microscopy Of Lipid-protein Samplesmentioning
confidence: 99%
“…Large numbers of fluorescence images were taken in different focal depths (Garstka et al, 2005(Garstka et al, , 2007Rumak et al, 2010Rumak et al, , 2012. This allowed the creation of computer-generated threedimensional structures in which the spatial layout of chlorophyll a fluorescence intensity was shown.…”
Section: Confocal Laser Scanning Microscopy Of Lipid-protein Samplesmentioning
confidence: 99%
“…tolerantes ao frio; e iii. tolerantes ao congelamento, as quais podem adquirir tolerância à geada após um período de exposição a temperaturas baixas não-congelantes em um processo adaptativo (GARSTKA et al, 2007 exposição prévia a temperaturas baixas não-congelantes, onde as plantas podem aumentar sua tolerância ao congelamento, ou sobreviver a temperaturas reduzidas (CHINNUSAMY et al, 2007). Este processo está associado a diversas alterações fisiológicas e bioquímicas: i. aumento dos níveis de açúcares, proteínas, aminoácidos e ácidos orgânicos; acúmulo de osmólitos e proteínas protetoras; ii.…”
Section: Introductionunclassified
“…Studies of cold−sensitive plants such as beans and cold−resistant plants, such as peas revealed, that differences in the protein and lipid composition of thylakoid membranes determine plants' sensitivity to low temperatures (Garstka et al 2007). The subcooling of pea and bean plants at low night−time temperatures and optimal day−time temperatures induced considerable changes in the chloroplast structures of both cold−sensitive and cold−resistant plants, but the observed processes were much slower in pea chloroplasts.…”
Section: Introductionmentioning
confidence: 99%